2006
DOI: 10.1176/ajp.2006.163.5.786
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia After a Selective Bilateral Lesion of the Globus Pallidus

Abstract: Case Presentation Mr. A, a 34-year-old man, came to our outpatient clinic for treatment of a major depressive episode. His history was also notable for polysubstance abuse and dependence in sustained remission, with prior abuse of alcohol, LSD, and other hallucinogens and prior dependence on marijuana, cocaine, opiates, and Ecstasy (MDMA [3,4-methylenedioxymethamphetamine]). He began using alcohol at age 9, marijuana at age 12, cocaine at age 13, opiates at age 20, and Ecstasy at age 21. He had a history of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 17 publications
5
58
0
2
Order By: Relevance
“…Long-term changes have been observed in the globus pallidus in narcotic addiction [Pearson et al, 1976]. Recent studies showed that the ventral tegmental area (VTA) project fibers to the globus pallidus as well as the nucleus accumbens (NAc), and NAc cells subsequently project to the ventral globus pallidus [Kalivas et al, 1999;Berridge, 2003;Wise, 2004;Miller et al, 2006]. The present data identified a possible expansion of LD blocks in the PTPRB 5 0 flanking region and near Ser127Gly (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Long-term changes have been observed in the globus pallidus in narcotic addiction [Pearson et al, 1976]. Recent studies showed that the ventral tegmental area (VTA) project fibers to the globus pallidus as well as the nucleus accumbens (NAc), and NAc cells subsequently project to the ventral globus pallidus [Kalivas et al, 1999;Berridge, 2003;Wise, 2004;Miller et al, 2006]. The present data identified a possible expansion of LD blocks in the PTPRB 5 0 flanking region and near Ser127Gly (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…However, a potential side effect of DBS in Parkinson's disease is the onset of apathy which is believed to be secondary to decreased pallidal responsivity, a finding in agreement with our observation of increased symptoms of fatigue in the context of reduced pallidal responses to reward stimuli. Similarly, a consistent body of clinical data on cerebrovascular insults has associated apathy with a disruption of the normal activity of the GPi and its related thalamo-frontal and prefrontal circuits [37], [38], characterized by the inability to initiate thoughts or behaviors [39]. Finally, studies from the animal literature strongly implicate the globus pallidus in reward, motivation, and effort-related choice behavior [40][42], all processes that have been found to be critically affected in CFS patients.…”
Section: Discussionmentioning
confidence: 91%
“…We suggest that these VP neuronal signals for reward components could be related to reports of activity in human posterior VP positively correlated with pleasant food images (17) and mechanisms by which opioid and related stimulation in a VP hotspot can modulate the hedonic impact of sensory rewards (33,36,77). Conversely, one could speculate that impairment of hedonic signals in NAc-VP pathways could contribute to clinical manifestations of anhedonia or incentive motivation impairment in depression and related disorders (78) or to dysphoria after lesions encroaching on the VP hotspot (79)(80)(81).…”
Section: Reward Component Separation By Population Segregation and Fimentioning
confidence: 99%